2016
DOI: 10.7759/cureus.567
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Care and Outcomes of Adjuvant Radiotherapy for Meningiomas: A Surveillance, Epidemiology, and End Results and Medicare Linked Analysis

Abstract: Background: The role of adjuvant stereotactic radiosurgery (SRS) and fractionated radiotherapy (XRT) are unknown in patients with resected meningiomas.Objective: To identify patterns of care and outcomes of adjuvant radiotherapy for meningiomas in the Linked Surveillance, Epidemiology, and End Results (SEER) Medicare data.Methods: A total of 1,964 patients older than 66 years included in the SEER-Medicare data, who were diagnosed with meningioma, and underwent craniotomy were included for analysis.Results: Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Gross total resection was also found to be a strong predictor of longer survival. 3,21,23 Additionally, in patients who did not undergo surgery, we found differences in survival based on the reason why no cancer-directed surgery was performed, with relatively worse survival in patients who refused surgery or for whom surgery was contraindicated due to another condition as compared to patients for whom surgery was not recommended. We also found, as expected, that uninsured patients had worse survival than insured patients.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Gross total resection was also found to be a strong predictor of longer survival. 3,21,23 Additionally, in patients who did not undergo surgery, we found differences in survival based on the reason why no cancer-directed surgery was performed, with relatively worse survival in patients who refused surgery or for whom surgery was contraindicated due to another condition as compared to patients for whom surgery was not recommended. We also found, as expected, that uninsured patients had worse survival than insured patients.…”
Section: Discussionmentioning
confidence: 78%
“…As in our previous work, we found that while pediatric meningiomas may include relatively more aggressive subtypes, young age is overall associated with reduced all-cause mortality. 4 In regard to sex, across all ages overall, meningiomas were more frequent in females than in males, but malignancy 19 and mortality 3,20,21 were greater in males than females. Also concordant with previous reports, black race and larger tumor size were found to be adverse prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical possibilities for such findings include local differences in medical care access and in particular to neuroimaging (e.g., head magnetic resonance imaging or head computed tomography), evaluations leading to coincidental discovery of tumors (migraine headache imaging), racial and socioeconomic disparities, and variance in population education levels. [3][4][5][6][7][8][9][10][11][12][13] The current study also noted a significant difference in treatment modalities utilized between registries for smallto medium-sized intracranial meningiomas, even when accounting for baseline differences in age and tumor size. For example, the distribution in tumor size between New Mexico and Greater California registries is nearly identical; however, the odds ratio for surgery was 1.5 times greater for the New Mexico population.…”
Section: Key Resultsmentioning
confidence: 49%
“…also found that the use of adjuvant SRS had remained stable over time in patients age >65 years between 2000 and 2010. 29 Additionally, the current analysis showed that private insurance and Medicare were associated with an increased likelihood of receiving SRS/HF-SRS, which may be a reflection of the referral patterns for insured patients. However, there was no association with academic versus nonacademic facility type.…”
Section: Discussionmentioning
confidence: 68%